PROTECTION FOR AUDITORS. (The Accounting Review, 1931)
The article focuses on protection for auditors. Montgomery says, wisely, that an auditor is forced to assume that in any case the balance sheet may be submitted to credit grantor. Perhaps it is a fortunate thing that such an assumption must be made. Otherwise a good many auditors would lose sight of the fact that the term "public accountant" if it means anything at all connotes responsibilities to third persons. The realization of his responsibility to the public is the auditor's best protection against personal liability for negligence. It has been urged that accountants carry insurance or incorporate and thus limit their liability. No worse contravention of their duties to third persons could be conceived. Another suggestion has been made that in certifying to balance sheets, the phrase "we hereby certify to you" be employed. This is even worse, if the auditor must limit or deny altogether his responsibility to persons other than his employee he would do better to label himself private accountant and issue no certificate.